Khảo sát các chất có hoạt tính sinh học trong nọc bọ cạp Heterometrus laoticus - Anh và cộng sự, Hoàng Ngọc (Vietnam Journal of Chemistry, 2014)
The scorpion Heterometrus laoticus, family Scorpionidae, are wide distributed in the west of the South of Vietnam. In the traditional medicine the alcohol extract of these scorpions is used as analgesic for muscle and bone pain. However, the venom of Vietnamese H. laoticus has not been studied untill now, so we carried out this work. Venom was collected from H. laoticus scorpions distribuding in the An Giang province. The crude venom of H. laoticus scorpions was separated into ten fractions by column chromatogaphy on Bio-Gel P 10. These fractions have different physic-chemical and biological properties. Tests on mice showed that six of these fractions are toxic. The most toxic fractions have molecular weight in range of 3-5 kDa and 6-8 kDa, that similar to neurotoxins isolated from scorpions, family Buthudae. Beside of the neurotoxins, in the H. laoticus venom there is toxins causing bleeding when inject them into mice. The crude venom of H. laoticus scorpion has activities against various kinds of microorganisms such as Staphylococcus aureus, Bacillus subtilus and Escherichia coli. This venom can be used in further to isolate the toxins and anti-bacterium compounds.